Cellular correlates of gray matter volume changes in magnetic resonance morphometry identified by two-photon microscopy [dataset] - Asan, Livia; Falfán‐Melgoza, Claudia; Beretta, Carlo Antonio; Sack, Markus; Zheng, Lei; Weber-Fahr, Wolfgang; Kuner, Thomas; Knabbe, Johannes (Universität, 2021)
This dataset accompanies the article of the same title in the journal Scientific Reports. It includes a) spreadsheets of data values for each plot ...
Grant number: Deutsche Forschungsgemeinschaft SFB 1158
Software: MATLAB, Fiji, ilastik
Gesehen am 11.02.2021
Keywords: Forschungsdaten; Datenbank